Psyllium supplementation is associated with changes in the fecal microbiota of horses - Mienaltowski, Michael J. (BMC Res Notes, 2020)
OBJECTIVE: Prophylactic supplementation of psyllium husk is recommended to enhance passage of ingested sand from the gastrointestinal tracts of horses. We hypothesized that psyllium supplementation would increase fecal sand passage and favorably alter bacterial populations in the hindgut. Six yearlings and six mature mares were fed a psyllium supplement in the diet daily for seven days. Voluntarily-voided feces were collected over the course of 29 days, prior, during, and after treatment. Feces were analyzed for acid detergent fiber (ADF) and acid detergent insoluble ash analyses. Microbial DNA was also isolated, and the V4 region of the 16S ribosomal RNA gene was PCR-amplified and sequenced using MiSeq technology. RESULTS: Fecal ADF concentration was greater in adults while silica concentration was greater in yearlings. Mature mare fecal ADF decreased during and just after supplementation but thereafter increased. No changes in silica levels were noted in either group over time. Fecal microbial population phylogenetic diversity was greatest mid-supplementation and lowest at 11 days post-supplementation. Functional profiles of the microbial communities presented some benefits for psyllium supplementation. These findings provide compelling evidence for further detailed studies of prophylactic psyllium supplementation.